2012
DOI: 10.1007/s00259-011-2034-3
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT versus MRI in patients with nonspecific pain of the hand and wrist – a pilot study

Abstract: In this initial comparison, SPECT/CT showed higher specificity than MRI in the evaluation of causative pathologies in patients with nonspecific wrist pain. However, MRI was more sensitive. Thus, SPECT/CT was shown to be a useful problem-solving tool in the diagnostic work-up of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 35 publications
1
27
0
4
Order By: Relevance
“…Huellner et al [57] recently reported a pilot retrospective study of 21 patients with non-specific hand and wrist pain, comparing SPECT-CT with MRI. MRI yielded a higher sensitivity of 86% vs 71% for SPECT-CT but a lower specificity of 20% vs 100% [57].…”
Section: Applications Of Single Photon Emission Ct-ct In the Upper Limbmentioning
confidence: 99%
See 2 more Smart Citations
“…Huellner et al [57] recently reported a pilot retrospective study of 21 patients with non-specific hand and wrist pain, comparing SPECT-CT with MRI. MRI yielded a higher sensitivity of 86% vs 71% for SPECT-CT but a lower specificity of 20% vs 100% [57].…”
Section: Applications Of Single Photon Emission Ct-ct In the Upper Limbmentioning
confidence: 99%
“…Huellner et al [57] recently reported a pilot retrospective study of 21 patients with non-specific hand and wrist pain, comparing SPECT-CT with MRI. MRI yielded a higher sensitivity of 86% vs 71% for SPECT-CT but a lower specificity of 20% vs 100% [57]. This pilot study supports the use of SPECT-CT as a problemsolving tool in patients with non-specific hand and wrist pain and reflects our own experience with SPECT-CT in the hand and wrist.…”
Section: Applications Of Single Photon Emission Ct-ct In the Upper Limbmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of further publications has addressed a range of more specific issues, such as SPECT/CT imaging of the feet and hands. SPECT/CT has been found to show good diagnostic accuracy in patients with obscure pain of the wrist or hand, being able to differentiate between osteoarthritic lesions, occult fractures and osteonecrosis [55][56][57][58]. A particularly elegant approach is that of combining SPECT/CT with arthrography, the latter yielding information on the intactness of articular cartilage and other soft-tissue structures such as the scapholunate and lunotriquetral ligaments [59].…”
Section: Differential Diagnosis Of Pain Associated With the Musculoskmentioning
confidence: 99%
“…Mit den aktuell verfügbaren SPECT-Geräten mit integrierter hochauflösender CT-Komponente, welche die oft unzureichende Ortsauflösung in der alleinigen SPECT kompensiert, wurden diese Probleme gelöst. Daher konnte die SPECT/CT bereits bei mehreren Indikationen ihren Nutzen im klinischen Alltag unter Beweis stellen [5,6,7,8].…”
Section: Hintergrundunclassified